2007
DOI: 10.1111/j.1540-8183.2007.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Stent Deployment: Understanding Stent Fracture in Percutaneous Pulmonary Valve Implantation

Abstract: Using finite element analysis of known stents, we were able to accurately predict stent fractures in the clinical situation. Furthermore, we have demonstrated that a stent-in-stent technique results in better device performance, which suggests a novel clinical strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…In this context, the usefulness of 3D-printed models was assessed specifically for evaluating shapes and sizes of the right ventricular outflow tracts (RVOTs) in patients that would be possible candidates for percutaneous pulmonary valve implantation (PPVI). As a Centre leading in the introduction of PPVI in clinic [12] as well as its evaluation with engineering analyses [13], 3D printing patient-specific models represented an additional valuable tool for determining PPVI suitability. A study [14] demonstrated that having access to 3D models in addition to cardiovascular magnetic resonance (CMR) imaging data resulted in cardiologists improving the indication of patients suitable for implanting the first PPVI device (Melody® valve, Medtronic Inc) (Figure 2).…”
Section: Early Experience: Testing a Novel Cardiovascular Devicementioning
confidence: 99%
“…In this context, the usefulness of 3D-printed models was assessed specifically for evaluating shapes and sizes of the right ventricular outflow tracts (RVOTs) in patients that would be possible candidates for percutaneous pulmonary valve implantation (PPVI). As a Centre leading in the introduction of PPVI in clinic [12] as well as its evaluation with engineering analyses [13], 3D printing patient-specific models represented an additional valuable tool for determining PPVI suitability. A study [14] demonstrated that having access to 3D models in addition to cardiovascular magnetic resonance (CMR) imaging data resulted in cardiologists improving the indication of patients suitable for implanting the first PPVI device (Melody® valve, Medtronic Inc) (Figure 2).…”
Section: Early Experience: Testing a Novel Cardiovascular Devicementioning
confidence: 99%
“…by guest on May 11, 2018 http://circinterventions.ahajournals.org/ Downloaded from were used for the platinum/10% iridium alloy stent and for the gold reinforcements. 9 The commercial software Abaqus/Standard (Simulia, Providence, RI) was used to run the simulations. A symmetrical initial stress condition formerly calculated was assigned to the stent model to account for residual stresses caused by the loading of the stent onto the catheter balloon in the catheterization laboratory.…”
Section: Fe Modelingmentioning
confidence: 99%
“…The extreme morphological variability of PPVI implantation sites 9 often results in asymmetrical expansion of the Melody device, 10 and combined with the complex 3-dimensional (3D) deformations experienced by the stent during both deployment and cardiac cycle form the basis of stent mechanical failure. Therefore, a thorough analysis of these parameters may facilitate prediction of stent fracture with greater accuracy and precision.…”
mentioning
confidence: 99%
“…To reproduce the golden coverings, an additional set of elements was modelled around the junctions and a structured hexahedral mesh was generated using 36,320 elements. Stent geometrical and material properties were provided by the manufacturer (Table 1; Schievano et al, 2007c Patient-specific stent deployments were replicated in Abaqus/Standard (Simulia, RI, USA) using nodal displacement boundary conditions (Fig. 3bottom).…”
Section: Understanding and Predicting Stent Fracturesmentioning
confidence: 99%
“…An optimised combination of different stent mechanical properties can help increase the strength of the device structure while at the same time reduce the stresses. This was computationally tested by expanding 2 PPVI stents 1 inside the other (Schievano et al, 2007c). The mechanical performance of the coupled device was compared with that of a single valved stent, expanded and cyclic loaded at the same conditions.…”
Section: Stent-in-stent As a Potential Solution To Stent Fracturesmentioning
confidence: 99%